Redox chemistry, solubility, and surface distribution of Pt(II) and Pt(IV) complexes dissolved in ionic liquids - Kolbeck, Claudia; Taccardi, Nicola; Paape, Natalia; Schulz, Peter; Wasserscheid, Peter; Steinrück, Hans-Peter; Maier, Florian (Journal of Molecular Liquids, 2014)
An X-ray photoelectron spectroscopy (XPS) study of Pt(II) and Pt(IV) complexes dissolved in ionic liquids (ILs) revealed the occurrence of a rich redox chemistry, which is partly induced by X-ray radiation. Depending on the IL anion either a reduction of Pt(IV) to Pt(II) in the case of ethylsulfate ([EtOSO])-based ILs, or an oxidation of Pt(II) to Pt(IV) in the case of bis[(trifluoromethyl)sulfonyl]imide ([TfN] )-based ILs was observed upon X-ray irradiation. Moreover, surface enrichment or depletion effects of the Pt complexes were deduced from angle-resolved XPS (ARXPS) data; while the Pt complexes dissolved in imidazolium-based ILs tended to deplete from the surface, in pyrrolidinium-based solutions a surface enrichment of the Pt complexes was observed. © 2013 Elsevier B.V. All rights reserved.